Identification of components in Kazakhstan honeys that correlate with antimicrobial activity against wound and skin infecting microorganisms - Pauline McLoone; Aizhan Zhumbayeva; Sofiya Yunussova; Yerkhat Kaliyev; Ludmila Yevstafeva; Susan Verrall; Julie Sungurtas; Ceri Austin; J. Will Allwood; Gordon J. McDougall (BMC, 2021)
Abstract Background Antimicrobial drug resistance is a major public health threat that can render infections including wound and skin infections untreatable. The discovery of new antimicrobials is critical. Approaches to discover novel antimicrobial therapies have included investigating the antimicrobial activity of natural sources such as honey. In this study, the anti-microbial activity and chemical composition of 12 honeys from Kazakhstan and medical grade manuka honey were investigated. Methods Agar well diffusion and broth culture assays were used to determine anti-microbial activity against a range of skin and wound infecting micro-organisms. Folin-Ciocalteu method was used to determine the total phenol content of the honeys and non-targeted liquid chromatography analysis was performed to identify components that correlated with antimicrobial activity. Results In the well diffusion assay, the most susceptible micro-organisms were a clinical isolate of Methicillin resistant Staphylococcus aureus (MRSA) and Enterococcus faecalis (ATCC 19433). Buckwheat & multi-floral honey from Kazakhstan demonstrated the highest antimicrobial activity against these two micro-organisms. Kazakhstan honeys with a buckwheat floral source, and manuka honey had the highest total phenol content. Non-targeted liquid chromatography analysis identified components that correlated with anti-microbial activity as hydroxyphenyl acetic acid, p-coumaric acid, (1H)-quinolinone, and abscisic acid. Conclusions The Kazakhstan honeys selected in this study demonstrated antimicrobial activity against wound and skin infecting micro-organisms. Compounds identified as correlating with antimicrobial activity could be considered as potential bioactive agents for the treatment of wound and skin infections.